Dramaturgi Kehidupan Pengemis Alun-Alun Kabupaten Jember (Lembaga Pengembangan Kinerja Dosen, 2023)
Poverty is a limitation for marginalized communities to join the world of work and is made more difficult by the complexity of company job qualifications (educational diplomas). High levels of economic need and few job opportunities make it difficult to survive, so being unemployed becomes something to do. In an effort to survive, tight conditions narrowed the mind's visibility so that all roads would be taken, resulting in the phenomenon of beggars spreading across the Jember city square. This research uses a phenomenological approach by understanding the phenomenon of begging which is discussed from the perspective of the perpetrator, which aims to reveal the real life of beggars in Alun-alun, Jember district. This research takes the perspective of Erfing Goffman's dramaturgical theory which views life as a stage for drama. The beggar label is not always about poverty. Some individuals use the